Diazaisoindigo bithiophene and terthiophene copolymers for application in field-effect transistors and solar cells - Du, Weiyuan; Yue, Wan; Onwubiko, Ada; Neophytou, Marios; Chen, Hu; McCulloch, Iain; Li, Weiwei; Chen, Hung Yang; Tian, Xuelin; Li, Cheng; Jellett, Cameron (My University, 2017)
Two donor–acceptor conjugated polymers with azaisoindigo as acceptor units and bithiophene and terthiophene as donor units have been synthesized by Stille polymerization. These two polymers have been successfully applied in field-effect transistors and polymer solar cells. By changing the donor component of the conjugated polymer backbone from bithiophene to terthiophene, the density of thiophene in the backbone is increased, manifesting as a decrease in both ionization potential and in electron affinity. Therefore, the charge transport in field-effect transistors switches from ambipolar to predominantly hole transport behavior. PAIIDTT exhibits hole mobility up to 0.40 cm2/Vs and electron mobility of 0.02 cm2/Vs, whereas PAIIDTTT exhibits hole mobility of 0.62 cm2/Vs. Polymer solar cells were fabricated based on these two polymers as donors with PC61BM and PC71BM as acceptor where PAIIDTT shows a modest efficiency of 2.57% with a very low energy loss of 0.55 eV, while PAIIDTTT shows a higher efficiency of 6.16% with a higher energy loss of 0.74 eV. Our results suggest that azaisoindgo is a useful building block for the development of efficient polymer solar cells with further improvement possibility by tuning the alternative units on the polymer backbone. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 2691–2699.
Keywords: Azaisoindigo; Conjugated polymers; Energy loss; Functionalization of polymers; High performance polymers; Solar cells; Solar cells